2013
DOI: 10.1590/s0034-75902013000300005
|View full text |Cite
|
Sign up to set email alerts
|

Legitimidade, governança corporativa e desempenho: análise das empresas da BM&F Bovespa

Abstract: This paper assesses how legitimacy conditions the market value of companies listed on the BM&F Bovespa. We specifically analyze how joining the Novo Mercado moderates the effect of legitimacy on company value. For such, 348 organizations were investigated between 2002 and 2007, which generated a total of 1357 observations. Adherence to the Novo Mercado, the prestige of board members and company reputation significantly affect market value. When the organizations are divided in accordance with the level of gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 38 publications
(25 reference statements)
1
12
0
13
Order By: Relevance
“…Our study suggests that universities with greater cognitive legitimacy are related to greater graduate employability, research productivity and social interest. These findings are consistent with previous research (Deephouse, 1996;Deephouse and Carter, 2005;Rossoni & Machado-Da-Silva, 2013).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Our study suggests that universities with greater cognitive legitimacy are related to greater graduate employability, research productivity and social interest. These findings are consistent with previous research (Deephouse, 1996;Deephouse and Carter, 2005;Rossoni & Machado-Da-Silva, 2013).…”
Section: Resultssupporting
confidence: 94%
“…After evaluating the results, the following propositions were made: a) institutionalized organizations with greater cognitive legitimacy are not related to greater resources; b) organizations with greater cognitive legitimacy have better organizational results. A study of the literature showed a link between overall organizational legitimacy and improved results and/or access to resources (Singh, Tucker, & House, 1986;Baum & Oliver, 1991;Hannan & Carroll, 1992;Pollock & Rindova, 2003;Rossoni & Machado-Da-Silva, 2013) but this relationship had not been sufficiently explored concerning cognitive legitimacy. In fact, most studies use other types of legitimacy (see Ruef & Scott, 1998;Bansal & Clelland, 2004;Cohen and Dean, 2005;Higgins & Gulati, 2003.…”
Section: Resultsmentioning
confidence: 99%
“…Chiu et al (2013) explain that most studies have sought to investigate the corporate behavior of organizations in diff erent areas of earnings behavior based on board interlocking. In Brazil, the research addresses the issue in terms of company legitimacy and value (Rossoni & Machado-da-Silva, 2013), political connections (Brey, Camilo, Marcon & Alberton, 2011;Brey, Camilo, Marcon & Bandeira-de-Mello, 2012;Camilo, Marcon & Bandeirade-Melo, 2012;Costa, Bandeira-de-Melo & Marcon, 2013;Macedo, Silva & Machado, 2015), company reputation (Rossoni & Guarrido, 2015), and earnings management (Ribeiro & Colauto, 2016). Rossoni and Machado-da-Silva (2013) evaluated how legitimacy conditions the market value of companies listed on the BM&FBOVESPA.…”
Section: Board Of Director Interlockingmentioning
confidence: 99%
“…Adicionalmente, esses trabalhos destacam que a legitimidade de uma organização não depende somente do grau de convergência com as instituições do ambiente, mas principalmente com o quanto tais instituições são legítimas (MEYER; ROWAN, 1977;SCOTT, 1998 MACHADO-DA-SILVA, 2013;TEIXEIRA, 2008). Pautado nesse autor, propomos que: · Definição 1 (legitimidade organizacional): "legitimidade é a percepção ou pressuposição generalizada de que as ações de uma entidade são desejáveis ou apropriadas dentro de algum sistema socialmente construído de normas, valores, crenças e definições" (SUCHMAN, 1995, p. 574, tradução nossa) 1 .…”
Section: Luciano Rossoniunclassified
“…Por fim, a quarta e última origem da legitimidade relacionada por Deephouse e Suchman (2008) é aquela vinculada aos laços e relacionamentos organizacionais, como, por exemplo, alianças estratégicas (DACIN; OLIVER; ROY, 2007;OLIVER, 2001), relações corporativas (COHEN; DEAN, 2005;GULATI, 2003;MACHADO-DA-SILVA, 2013;SANDERS;TUSCHKE, 2007), joint ventures (DEEDS;MANG;FRANDSEN, 2004), parcerias institucionais (SINGH; TUCKER; HOUSE, 1986), relações com stakeholders (CHOI; WANG, 2009) e relações diretas com estâncias de avaliação (CATTANI et al, 2008;MACHADO-DA-SILVA, 2010). Esses estudos partem da premissa de que os relacionamentos são importantes porque uma organização pode legitimar-se por meio dos laços com organizações tidas como legítimas (GALASKIEWICZ, 1985).…”
Section: Níveis Objetos E Origens Da Legitimidade Organizacionalunclassified